The Development Pop-Up Books To Improve Children’s Language Skills - Karina Bunga Pratiwi; Sugito Sugito; Marianus Subandowo (Universitas Negeri Malang, 2020)
This study aimed to determine the improvement of language learning ability by using a pop-up book as learning media. Early childhood education is carried out by educators and parents in the process of care and education for children by creating an aura and environment where children can use experiences that provide opportunities to know and understand learning experiences that they have gained from the environment, from the way, using and experimenting that goes on repeatedly and maybe for the whole potential and intelligence of the child. The learning media was prepared using the ADDIE model with the developmental steps, namely analysis, development, implementation, and evaluation. The instruments used in the data study consisted of: validation of material, media, peers and results for sharing and the results of developing Pop Up Book media. From the learning outcomes of students through academic techniques namely daily development achievement scale shows that the development of the students in accordance with the expectations and activeness of students is very good. This shows that the product development of the Pop Up Book media was proper and very feasible and could attract the students in the learning process.AbstrakPenelitian ini bertujuan untuk mengetahui peningkatan kemampuan belajar bahasa dengan menggunakan buku Pop-up sebagai media pembelajaran. Pendidikan anak usia dini dilakukan oleh pendidik dan orang tua dalam proses pengasuhan dan pendidikan untuk anak-anak dengan menciptakan aura dan lingkungan di mana anak-anak dapat menggunakan pengalaman yang memberikan peluang untuk mengetahui dan memahami pengalaman belajar yang telah mereka peroleh dari lingkungan, dari cara, menggunakan dan bereksperimen yang berlangsung berulang kali dan mungkin untuk seluruh potensi dan kecerdasan anak. Media pembelajaran dikembangkan menggunakan model ADDIE dengan langkah pengembangan, yaitu analisis, pengembangan, implementasi, dan evaluasi. Instrumen yang digunakan dalam analisis data terdiri dari: validasi bahan, media, rekan dan hasil untuk berbagi dan hasil pengembangan media Pop-up Book. Hasil belajar siswa melalui teknik akademik yaitu skala pencapaian perkembangan harian menunjukkan bahwa perkembangan siswa sesuai dengan harapan dan keaktifan siswa sangat baik. Ini menunjukkan bahwa pengembangan produk media Pop-up Book layak sangat layak dan dapat menarik siswa dalam proses pembelajaran.